Շարահյուսական միավորների և կապակցության եղանակների հարաբերակցության շուրջ - Թելյան, Լ. Գ.
В специальной литературе, посвященной синтаксису современного армянского языка, нет единого подхода к интерпретации вопроса соотношений видов синтаксической связи / согласование, управление, примыкание, «зависимость»/, т. е. распределения сфер их действия. Это обусловлено разными оценками характера соединяющихся единиц и особенностей их синтаксической связи. Настоящая статья – опыт представления различий в интерпретации нескольких таких конструкций / подлежащее-сказуемое, определение-определяемое, предложно – послеложная конструкция/. In the special literature devoted to the syntax of the modern Armenian language, there is no unified approach to the interprettation of the issue of the ratio of the types of syntactic connection (agreement, control, adjacency, "dependence"), i.e. the distribution of their spheres of action. This is due to different assessments of the nature of the connecting units and the peculiarities of their syntactic connection. The present article is an experience in presenting the differences in the interpretation of several such constructions (subject-proposal, definitional-definitive, prepositional-postpositional construction).
Keywords: Լեզվաբանություն